Measuring Technology and Mechatronics Automation in Electrical Engineering - Hou, Zhixiang (Lecture Notes in Electrical Engineering, 2012)
Measuring Technology and Mechatronics Automation in Electrical Engineering includes select presentations on measuring technology and mechatronics automation related to electrical engineering, originally presented during the International Conference on Measuring Technology and Mechanatronics Automation (ICMTMA2012). This Fourth ICMTMA, held at Sanya, China, offered a prestigious, international forum for scientists, engineers, and educators to present the state of the art of measuring technology and mechatronics automation research.